Lokalisationsbesonderheiten der Festen Bitumen in Doleriten der Roten Anhöe (die Republik Chakassija); Проблемы геологии и освоения недр; Т. 2 - Morozov D. I. (Geology, mining and petroleum engineering, 2013)
Заглавие с экрана